2015
DOI: 10.1371/journal.pone.0140509
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Innovative Personality-Mindset Profiling Tool to Guide Culture-Change Strategies among Different Healthcare Worker Groups

Abstract: IntroductionImportant culture-change initiatives (e.g. improving hand hygiene compliance) are frequently associated with variable uptake among different healthcare worker (HCW) categories. Inherent personality differences between these groups may explain change uptake and help improve future intervention design.Materials and MethodsWe used an innovative personality-profiling tool (ColourGrid®) to assess personality differences among standard HCW categories at five large Australian hospitals using two data sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…A recent systematic review on vancomycin education strategies found that interventions which used multimodal strategies, a guideline, educational meetings and dissemination of educational materials had a greater effect than individual interventions on improving vancomycin use . The profession‐specific education strategies identified in our study by educators and recipients align with outcomes of a study that used a personality profiling tool to understand the requirements of different health professions in order to increase knowledge and successfully change behaviour . Similar to the current study, doctors required a personalised approach, with strong emphasis on the education being evidence‐based.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A recent systematic review on vancomycin education strategies found that interventions which used multimodal strategies, a guideline, educational meetings and dissemination of educational materials had a greater effect than individual interventions on improving vancomycin use . The profession‐specific education strategies identified in our study by educators and recipients align with outcomes of a study that used a personality profiling tool to understand the requirements of different health professions in order to increase knowledge and successfully change behaviour . Similar to the current study, doctors required a personalised approach, with strong emphasis on the education being evidence‐based.…”
Section: Discussionsupporting
confidence: 62%
“…Similar to the current study, doctors required a personalised approach, with strong emphasis on the education being evidence‐based. In contrast, nurses required a collective approach, with education delivered through in‐services …”
Section: Discussionmentioning
confidence: 99%
“…Participants regarded doctors as generally resistant to external rules, which they see as a challenge to their clinical autonomy and self-perception as independent thinkers [36]. In relation to IPC they may exercise autonomy, either by taking it very seriously (exemplary practice) or by choosing to remain ignorant or dismissive of basic IPC precautions, which participants interpreted as evidence of a perceived entitlement to decide, for themselves, what is important.…”
Section: Discussionmentioning
confidence: 99%
“…74 Current AMS programmes that target junior medical staff often fail to recognise the difficulties in challenging this ingrained cultural hierarchy. 71,72,74 As medical personnel value autonomy, 75 the success of AMS initiatives is maximised when developed within a framework of collaboration and collegiality. 76 Ultimately, for AMS to be effective, initiatives need the sustained endorsement of senior clinicians and engagement by the hospital leadership.…”
Section: The Bundles Of Carementioning
confidence: 99%